Synthesis, characterization and evaluation of antituberculosis activity of some hydrazones - (:unkn) unknown (My University, 2002)
Several new hydrazone derivatives were prepared by the reaction of some active hydrogen compounds with the diazonium salts of 4-amino-3,5-di/1,3,5-trimethylpyrazoles at 0-5°C. Structures of the new substances were confirmed using UV, IR, 1H NMR, 13C NMR and EI-mass spectral data. In vitro antituberculosis activity of these compounds were tested on Mycobacterium tuberculosis H37Rv at 6.25 μg/ml. Both hydrazone products, ethyl 2-[(3,5-dimethylpyrazole-4-yl)hydrazono]-3-oxobutyrate (3d) and methyl 2-[(3,5-dimethylpyrazole-4-yl)hydrazono]-4-methoxy-3-oxobutyrate (3e) showed 29 and 28% inhibition against M. tuberculosis, respectively. © 2002 Éditions scientifiques et médicales Elsevier SAS. All rights reserved.
Keywords: 4-Amino-3,5-di/1,3,5-trimethylpyrazoles; Antituberculosis activity; Hydrazones